Where Dopaminergic and Cholinergic Systems Interact: A Gateway for Tuning Neurodegenerative Disorders - Amalric, Marianne; Pattij, Tommy; Sotiropoulos, Ioannis; Silva, Joana M.; Sousa, Nuno; Ztaou, Samira; Chiamulera, Cristiano; Wahlberg, Lars U.; Emerich, Dwaine F.; Paolone, Giovanna (Frontiers in Behavioral Neuroscience, 2021)
Historically, many investigations into neurodegenerative diseases have focused on alterations in specific neuronal populations such as the loss of midbrain dopaminergic neurons in Parkinson’s disease (PD). It has, however, become increasingly clear that mammalian brain activities, from executive and motor functioning to memory and emotional responses, are strictly regulated by the integrity of multiple interdependent neuronal circuits. Among subcortical structures, the dopaminergic nigrostriatal pathway and the cholinergic innervations from the basal forebrain, play pivotal roles in orchestrating cognitive and non-cognitive symptoms in Alzheimer’s disease (AD) and PD. Understanding the functional interactions of these circuits and the consequent neurological changes that occur during degeneration provides new opportunities to understand the fundamental inter-workings of the human brain as well as develop new potential treatments for patients with dysfunctional neuronal circuits. Here we provide an update on progress in several specific areas related to interactions between cholinergic and dopaminergic systems by summarizing several presentations from the 18th biennial meeting of the European Behavioral Pharmacology Society held in Braga, Portugal in August 2019. These discussions include descriptions of (1) stress as a regulator of proteostasis and RNA homeostasis in AD, (2) striatal cholinergic interneurons and PD, (3) dopaminergic and cholinergic modulation of impulse control, and (4) the use of an implantable cell-based system for drug delivery directly the brain.